Associations Between Physical Activity and Multiple Maternal Health Outcomes Among Pregnant Women: A Cross-Sectional Study - Tri Nur Jayanti; R. Nety Rustikayanti; Inggrid Dirgahayu (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2026)
important role in maintaining maternal health. However, inappropriate activity levels may be associated with various adverse maternal outcomes. Previous studies have often focused on single health outcomes, limiting understanding of how physical activity relates to multiple maternal conditions within the same population. Objective: This study aimed to comprehensively examine the associations between physical activity levels and multiple maternal health outcomes, including constipation, low back pain (LBP), blood pressure, chronic energy deficiency (CED), and anemia, among pregnant women. Methods: This cross-sectional correlational study involved 251 pregnant women consecutively recruited from two community health centers. Physical activity was assessed using the Pregnancy Physical Activity Questionnaire (PPAQ), while constipation, LBP, blood pressure, CED, and anemia were measured using the Constipation Assessment Scale (CAS), Numeric Rating Scale (NRS), and a standardized checklist form. Data were analyzed using Chi-square and Fisher’s exact tests, with odds ratios (ORs) and 95% confidence intervals (CIs) calculated for significant associations. Results: Most respondents reported moderate levels of physical activity. Physical activity level was significantly associated with LBP severity (p = 0.020), with women engaging in vigorous activity showing higher odds of severe LBP compared with those performing sedentary to moderate activity (OR = 1.83; 95% CI: 0.94–3.54). No statistically significant associations were observed between physical activity level and constipation, blood pressure, CED, or anemia. Conclusion: Low back pain was the only maternal health outcome significantly associated with physical activity level in this study. These findings highlight the importance of antenatal care interventions that prioritize screening for LBP, assessment of physical workload patterns, and guidance on safe and balanced physical activity to prevent severe LBP during pregnancy.